Proposal of Microsquama subgen. nov. for Nephroselmis pyriformis (Carter) Ettl (Nephroselmidophyceae, Chlorophyta). Issue 4 (3rd June 2013) - Yamaguchi, Haruyo; Nakayama, Takeshi; Inouye, Isao
Summary A new subgenus, Microsquama, is proposed for Nephroselmis pyriformis based on its phylogenetic position and some ultrastructural characters, such as the absence of large stellate scales. Other species of the genus are classified in the subgenus Nephroselmis.